RACOLLECTION OF A CLINICAL CASE OF ACUTE ADRENAL INSUFFICIENCY IN A YOUNG PATIENT DUE TO PULMONARY TUBERCULOSIS - Negmatova, Gulzoda Shukhratovna; Mansurova, Gulsum Zaydinovna; Ibragimov, Kamronbek Uktam o‘g‘li; Abdiyev, Lazizbek Sobir oʻgʻli (Educational Research in Universal Sciences, 2024)
Acute adrenal insufficiency (AIF) is an urgent condition caused by a sudden and/or significant decrease in the functional reserves of the adrenal cortex. SCI is quite rare - 2-3% among severely ill patients in intensive care units. ACI can develop in patients with previously undiagnosed primary chronic adrenal insufficiency (CAI) when exposed to severe stress (trauma, surgery, blood loss) and often ends in death. Chronic primary adrenal insufficiency (PAI) was first coined by Addison and is, therefore, termed Addison’s disease [1]. The prevalence rate of Addison’s disease in western countries is 82–144 cases per million people [2].